(untitled) (International Journal of Environmental Sciences, 2025)
Background:Lesions of the major salivary glands pose a diagnostic challenge due to their diverse pathology and overlapping imaging features. While conventional ultrasound is widely used, its limitations in reliably distinguishing benign from malignant lesions necessitate adjunctive modalities. Ultrasound elastography, by evaluating tissue stiffness, may improve diagnostic precision. Objective:To evaluate and characterize lesions of the major salivary glands using grayscale ultrasound, color Doppler, and ultrasound elastography (strain and shear wave modalities), and to correlate these findings with clinico-pathological diagnosis. Methods:In this prospective observational study, 74 patients with clinically suspected salivary gland lesions underwent grayscale ultrasound, Doppler imaging, strain elastography (eSie Touch), and shear wave elastography (VTQ and VTIQ). Imaging findings were compared with histopathological or cytological results. Diagnostic accuracy parameters were calculated, and ROC analysis was used to determine optimal elastographic cut-offs. Results:Of the 74 lesions evaluated, 66 (89.2%) were benign and 8 (10.8%) malignant. Grayscale ultrasound alone yielded 62.5% sensitivity and 69.7% specificity. Combining ultrasound with elastography improved sensitivity to 87.5%, specificity to 78.8%, and overall diagnostic accuracy to 79.7%. Malignant lesions exhibited significantly higher stiffness values on VTQ and VTIQ (p < 0.001). ROC analysis showed VTQ >40.5 kPa and VTIQ >3.7 m/s as optimal cut-offs. Conclusion:Ultrasound elastography significantly enhances diagnostic accuracy in salivary gland lesion evaluation when used alongside conventional imaging. Its integration into routine imaging protocols can improve lesion stratification and reduce unnecessary invasive procedures.